Tennyson's language - Hair, Donald S. (University of Toronto Press, 1991)
Hair offers a significant contribution to the development of linguistic theory in Britain while also providing some close readings of key passages of Tennyson's work and examinations of the poet's faith and views of society.
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Language.; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Knowledge -- Language and languages.; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Langage.; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Et le langage et les langues.; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892; Tennyson, Alfred, -- (1809-1892) -- Langue.; Tennyson, Alfred.; Language and languages -- Philosophy -- History -- 19th century.; Langage et langues -- Philosophie -- Histoire -- 19e siècle.; POETRY -- English, Irish, Scottish, Welsh.; Language and languages; Language and languages -- Philosophy; Sprache; Philosophie du langage -- Histoire.; 1800-1899; English poetry; History